RANCANG BANGUN SISTEM PENGAMANAN GEDUNG YANG DIKONTROL MELALUI APLIKASI ANDROID BERBASIS IoT - Fendi Pradana; Ardi Amir (Foristek, 2020)
Building or home security systems at this time are needed because there are still many security systems that can trigger crime, one of which is the use of padlock or conventional door locks and security that has not worked automatically. A security system is needed which has a high level of security and is automatic so that it does not bother users. Security systems are often a problem, namely the low level of security, how to use is not easy, and not automatic. The way to overcome this problem is to create a security system that has tight security, easy to use, works continuously automatically and can be connected to the user's mobile phone. Based on research that has been made this security system shows one of the security systems that have a high level of security because it is equipped with an infrared sensor that serves to detect the presence of humans, the camera takes pictures if the infrared sensor detects humans, a fingerprint sensor that functions as access to open the door and all The sensor works automatically and continuously and can be connected to mobile phones through the internet, this security system works well and can be relied upon.